ANTIMICROBIAL ACTIVITIES OF METHANOL EXTRACT FROM UNIDENTIFIED SPONGE ASSOCIATED BACTERIA IN LEMUKUTAN ISLAND, KALIMANTAN BARAT - Risa Nofiani; Siti Nurbetty; Ajuk Sapar (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
The increase of issues on the antibiotics resistant pathogenic bacteria has triggered high exploration for new antimicrobial compounds. One of the potential sources is sponge-associated bacteria. The aim of this study was to get sponge-associated bacteria extract containing antimicrobial activities. On the basis screening of antimicrobial activity using by streaking on agar medium, there were two potential isolates with antimicrobial activities namely LCS1 and LCS2. The two isolates were cultivated,then secondary metabolite product were extracted using methanol as a solvent. Minimum inhibitory concentrations (MICs) of extract LCS 1 were 1,000 μg/well for S. aureus, 950 μg/well for Salmonella sp.and 800 μg/well for Bacillus subtilis. Minimum inhibitory concentrations of extract LCS 2 were 500 μg/well for S. aureus, 1,050 μg/well for Salmonella sp., 750 μg/well for Bacillus subtilis, 350 μg/well for P. aeruginosa, 750 μg/sumur terhadap B. subtilis. Based on the MIC values, the two assay extracts have a relatively low antimicrobial activity. Keywords:Antimicrobial,Sponges associated bacteria,MICs